2021
DOI: 10.1088/1361-6579/abf1b1
|View full text |Cite
|
Sign up to set email alerts
|

Fractional-order model representations of apparent vascular compliance as an alternative in the analysis of arterial stiffness: an in-silico study

Abstract: Recent studies have demonstrated the advantages of fractional-order calculus tools for probing the viscoelastic properties of collagenous tissue, characterizing the arterial blood flow and red cell membrane mechanics, and modeling the aortic valve cusp. In this article, we present novel lumpedparameter equivalent circuit models of the apparent arterial compliance using a fractional-order capacitor (FOC). FOC, which generalizes capacitors and resistors, displays a fractionalorder behavior that can capture both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Bearing this in mind, recently, an alternative modeling approach of the apparent compliance was proposed in (Bahloul and Kirati, 2021 ) where fractional-order tools were investigated to represent the complex phenomena underlying the apparent arterial compliance. In (Bahloul and Kirati, 2021 ), the authors presented fractional-order models to describe the dynamic relationship between aortic blood pressure and volume, describing the apparent vascular compliance. The proposed model employs fractional-order capacitor elements to lump the complex and frequency dependence characteristics of arterial compliance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bearing this in mind, recently, an alternative modeling approach of the apparent compliance was proposed in (Bahloul and Kirati, 2021 ) where fractional-order tools were investigated to represent the complex phenomena underlying the apparent arterial compliance. In (Bahloul and Kirati, 2021 ), the authors presented fractional-order models to describe the dynamic relationship between aortic blood pressure and volume, describing the apparent vascular compliance. The proposed model employs fractional-order capacitor elements to lump the complex and frequency dependence characteristics of arterial compliance.…”
Section: Methodsmentioning
confidence: 99%
“…In recent decades, fractional-order models have surfaced as potential techniques that compromise between accuracy and computational cost for large-scale problems in different fields (Bahloul and Kirati, 2021 ). In particular fractional-order differential equations have been considerably explored in modeling complex biological systems (Magin, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples are the model of blood flow in viscoelastic vessels [10,11] and the model of heat and mass transfer through an arterial segment, which takes into account the interaction with a magnetic field [12]. Fractional derivatives are used to obtain a more realistic prediction of pulse wave forms, which involves the development of parameter identification procedures [13,14]. The latter task has become especially relevant in recent years with the development of computer technology and increasing interest in inverse problems.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the power-law behavior has been demonstrated in describing human soft tissues viscoelasticity and characterizing the elastic vascular arteries. In-vivo and in-vitro experimental studies have pointed that fractional-order calculus-based approaches are more decent to precisely represent the hemodynamic; the viscoelasticity properties of soft collagenous tissues in the vascular bed; the aortic blood flow; red blood cell (RBC) membrane mechanical properties and the heart valve cusp [16] [19] . Consistent with the ability of fractional-order models to fit temporal dynamics, Belkhatir et al in [20] have shown that the fractional-order model can yield better fit to Blood-Oxygenation-Level-Dependant (BOLD) signals measured with fMRI when compared with the original integer-order NVC model proposed by Friston et al in [5] .…”
Section: Introductionmentioning
confidence: 99%